The Influence of E-Commerce, Digital Payments, and Accounting Information Systems on Micro Business Performance - Adila Hikmaini; Lihan Rini Puspo Wijaya; Dewi Zakia; Sri Astuti; Arif Makhsun (LPPM STIE KRAKATAU, 2026)
This study aims to examine the influence of e-commerce, digital payments, and Accounting Information Systems (AIS) on the performance of micro-enterprises in the culinary sector in Bandar Lampung City. This study employed a quantitative approach using primary data collected through questionnaires distributed to micro-business owners. A total of 429 valid responses were obtained from 562 distributed questionnaires using an accidental sampling technique. The data were analyzed using multiple linear regression with the assistance of SPSS version 26. The findings indicate that e-commerce, digital payments, and AIS have a positive and significant effect on micro-business performance, both partially and simultaneously. Among the examined variables, e-commerce demonstrated the strongest influence, followed by digital payments and AIS. These findings indicate that digital technology adoption supports market expansion, transaction efficiency, and more effective financial management. The utilization of digital technologies plays an important role in improving micro-business performance by enhancing operational effectiveness and competitiveness. Limitations: This study is limited to culinary micro-enterprises in Bandar Lampung City, which may restrict the generalizability of the findings to other sectors and regions. This study contributes empirical evidence regarding the role of digital technology adoption in improving micro-business performance and provides practical insights for entrepreneurs and policymakers in developing digital transformation strategies.